Spatiotemporal evolution of long-term slow slip events at the Hikurangi Subduction Zone, New Zealand (2021-2023): implications for seismic activity - Yan, Li; Sun, Yanling; Li, Meng; El-Mowafy, Ahmed; Lu, Tieding (KeAi Communications Co, 2025)
Various slow slip events (SSEs) with distinct characteristics have been detected globally, particularly in regions with dense Global Navigation Satellite Systems (GNSS) networks. In the Hikurangi subduction zone of New Zealand, SSEs frequently occur alongside seismic activity, especially in the Manawatu and Kapiti regions. This study analyzes the 2021–2023 Kapiti-Manawatu long-term SSE using daily displacement data (2019–2023) from 53 GPS stations. The network inversion filter (NIF) method is applied to extract slow slip signals, revealing spatial migration with alternating slip between Kapiti and Manawatu, characterized by distinct phases of acceleration and deceleration. Manawatu exhibits higher slip rates, exceeding 4 cm/month, with greater cumulative slip and surface displacement than Kapiti. A moderate temporal correlation (coefficient 0.59) between seismic activity in the region and slip acceleration in Manawatu suggests that seismic events may contribute to the slip, while no significant correlation is observed in Kapiti.